Construction of FeOOH modified CoMxOy (M = Mo, W, V) on nickel foam for highly efficient oxygen evolution reaction. Issue 4 (25th January 2023) - Wen, Tingting; Wang, Limin; Gong, Yaqiong
Abstract : The synthesized FeOOH–CoMoO4 electrode exhibited significant electrocatalytic performance for the OER in KOH alkaline solution. Abstract : Design and synthesis of a highly efficient OER catalyst is the key to improve the efficiency of hydroelectrolysis for hydrogen production. In this paper, a rational approach to improve the catalytic performance of CoMoO4 nanomaterial was reported. A nanoflower structured CoMoO4 precursor was synthesized on nickel foam using a typical hydrothermal method. Then, CoMoO4 /NF was etched through brief immersion in iron nitrate solution at room temperature to produce FeOOH–CoMoO4 /NF. The unique 3D structure of FeOOH–CoMoO4 /NF could availably promote interfacial electron transfer as well as effectively provide abundant active sites, and it exhibited excellent electrocatalytic activity. FeOOH–CoMoO4 /NF requires an overpotential of 209 mV to achieve a current density of 10 mA cm −2 . Meanwhile, the material FeOOH–CoMoO4 /NF exhibits excellent catalytic durability of up to 24 h, which is promising for practical applications in energy conversion. Thus, this work may offer a viable strategy to assemble remarkable OER electrocatalysts.